Relative frequency of dentigerous cyst in Iranian population: A 20-year retrospective study - Ali Lotfi; Sina Shirkavand; Sepideh Mokhtari; Saman Salehi Zalani; Saede Atarbashi-Moghadam (Wolters Kluwer Medknow Publications, 2019)
Purpose: Dentigerous cyst (DC) is the most common type of developmental odontogenic cysts which apparently develops via accumulation of fluid between the reduced enamel epithelium and crown of the tooth. The aim of this study is to analyze the frequency of DC in Iranian population. Materials and Methods: The files of oral pathology, Shahid Beheshti University of Medical Sciences, served as the source of the materials from 1992 to 2012 for this study. All lesions diagnosed as DCs were subjected to microscopic reevaluation. Patient's age, sex, location, and microscopic characteristics were recorded. Based on these data, a descriptive statistical analysis was performed using SPSS 19 software (IBM SPSS Statistics 19, New York, United States) and the results with P < 0.05 were considered as significant. Results: DC accounted for 34.37% of all odontogenic cysts of the jaws during the 20-year period. The mean age of patients was 24.72 years and most cases are diagnosed in the second and third decades of life. The male-to-female ratio was 1.52. About 73.89% of all lesions had occurred in the mandible and 26.11% in maxilla. DCs showed Vickers and Gorlin (ameloblastomatous) changes in 2.36% of cases. The mean age was significantly lower in the premolar area (P = 0.00). Conclusion: Age, sex, and location of DCs in Iranian population are similar to previous studies. In addition, the age of occurrence for this lesion in the premolar region was relatively lower than at other sites. Although the risk of ameloblastic change is low, it should be considered as an important issue.